Origin Identification of the Sauce-Flavor Chinese Baijiu by Organic Acids, Trace Elements, and the Stable Carbon Isotope Ratio - Jian Zhang; Zhiqiang Tian; Yiqian Ma; Feilong Shao; Jialing Huang; Hao Wu; Ling Tian (Journal of Food Quality)
Sauce-flavor baijiu is a popular Chinese baijiu. To avoid adulteration and market cheating, this study aims to develop a new, reliable, and accurate traceability system for characterization of the geographical origins. Totally, 100 samples collected from seven regions in Guizhou Province of China are analyzed, involving 13 trace elements, 5 organic acids, and stable carbon isotope composition of acetic acid. Based on these data, a geographical classification model is established. The origin accuracy is found to reach as high as 83%, thus providing a useful technique for authentication of the sauce-flavor baijiu and contributing to the healthy development of the baijiu industry in China.